A Promising Approach for Determining Neutrino Mass Hierarchy by Using Supernova Neutrino Detections - Gexing Li; Zhihong Li (The Astrophysical Journal)
The determination of neutrino mass hierarchy is crucial for particle physics, astrophysics, and cosmology. In this work, we propose an easy-to-use method to determine the neutrino hierarchy based on core-collapse supernova (CCSN) neutrino detections. By analyzing the expected event rates of the neutrino burst at a terrestrial water Cherenkov detector, we found that the event rates predicted by the normal and inverted hierarchy models have marked differences in the neutrino energy range 10 ∼ 20 MeV and the postbounce time <0.5 s. Within this specific energy and time range, the analytical relationship between the cumulative event number and proto–neutron star (PNS) baryon mass is extracted. Based on the normal and inverted hierarchy models, two different PNS masses can be inferred from this relationship by using the time profile of neutrino events. Then, the neutrino hierarchy can be determined by comparing the PNS mass inferred from the neutrino detections and the electromagnetic or gravitational-wave channels. Furthermore, the nonadiabatic part of the Mikheyev–Smirnov–Wolfenstein flavor conversions may also be quantified with this method, which would be very helpful for the studies of the explosion mechanism and nucleosynthesis of CCSNe.